Cephalometric Norms of Erbil Kurdish Adults - Bootan A. Mustafa Chalabee; Bayan A. Hassan (Polytechnic)
Ethical group might have differential skeletal forms, thus cephalometric analysis and orthodontic material have been developed for specific ethnic groups which might be different for Kurdish Ethics. Objectives: This study is to determine the cephalometric norms of an Erbil Kurdish population according to Steiner analysis, who attend to Tishk Hospital/Diagnosis Department Materials and Methods: In this cross-sectional study, 48 lateral cephalograms of adult orthodontic subjects between 20 and 29 years with normal occlusion, and with no previous orthodontic treatment were evaluated. Lateral cephalograms were traced and analyzed based on Steiner’s cephalometric parameters. Data were analyzed using SPSS. Differences between Erbil Kurdish and Steiner’s norms were analyzed using one-sample t-test (P < 0.05). Results: The SNA, ML-NSL (Mandibular Line to NS line), U1-NA (both angular and linear measurements), interincisal angle, L1-NB (angular only), Pog-NB, L1-Pog//NB, Ls-SL, and Li-SL values were significantly different between the Erbil Kurdish population and Steiner’s norms (P < 0.05). No significant differences existed in Occl-SN (occlusal plane to SN) and L1-Nb (linear only), SNB, and ANB between the Erbil Kurdish population and the Steiner’s norms (P > 0.05). Conclusions: Cephalometric norms for Erbil Kurdish adults are different from those of Steiner’s norms. The norms obtained in our study can be used for orthodontic treatments and orthognathic surgeries in Erbil Kurdish population.